Dampak Pengungkapan Sustainability Report terhadap Kinerja: Komparasi Kinerja Pasar dan Kinerja Akuntansi - Kartikasari, Amanda Dwi; Laela, Sugiyarti Fatma (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This study aims to analyze the effect of Sustainability Report (SR) disclosure on company performance. Research Methodology: This study uses data from 170 manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. A total of 832 book years were analyzed using the panel data regression method. Performance is measured using earnings per share (EPS), which reflects market performance, and Return on Equity (ROE) and Return on Assets (ROA), which reflect accounting performance. Results: The findings show that SR disclosure positively affects EPS performance. SR disclosure has a marginal influence on ROE performance with an alpha test level of 10%. However, SR disclosure does not have a significant effect on ROA performance. Although internal SR disclosure does not affect performance, it has been proven to elicit a response from the market. Limitations: Sustainability Disclosure in this study was measured using a dummy variable. Consequently, it is less comprehensive to assess the quality of sustainability practices. Contribution: The findings strengthen the literature on the influence of sustainability disclosures on market performance. The challenge is to empirically prove that market performance should have an impact on accounting performance in the long term.